Pandrug Resistance (PDR), Extensive Drug Resistance (XDR), and Multidrug Resistance (MDR) among Gram-Negative Bacilli (Bangladesh Journal of Infectious Diseases, 2015)
No Abstract AvailableBangladesh Journal of Infectious Diseases 2014;1(2):22-23